Erythema multiforme: A retrospective study of etiologies, clinical manifestations, and treatments - Tugce Gungor; Salih Gumru; Birsay Gumru (Elsevier, 2024)
Background/purpose: Erythema multiforme (EM) is considered a hypersensitivity reaction associated with drugs and infections, and remains underestimated due to the lack of precise classification and diagnostic criteria. The aim of this study was to evaluate the triggering factors and clinical manifestations of EM and to present our experience in the diagnosis and management of this disorder. Materials and methods: All patient records were reviewed, and records of patients admitted, diagnosed, and treated with EM were retrieved. Data on age, gender, medical history, triggering factor(s), clinical form, mucosal/cutaneous involvement, affected oral site(s), recurrence, and treatment were collected. The data were analyzed statistically at a significance level set at P < 0.05. Results: A total of 36 EM patients were studied. The triggering factor was identified as infection in 25 %, drugs in 16.7 %, infections and drugs in 41.7 %, and none in 16.7 % of the 36 EM patients. EM minor was diagnosed in 77.8 % of the patients. Labial mucosa (86.1 %) was the most commonly affected oral site. Most patients were treated with topical steroids (25 %). No significant differences were detected between demographic and clinical characteristics with regards to gender, triggering factor, and the number of affected oral sites (P > 0.05). Conclusion: The results of this study, based on the data from 36 EM patients with oral involvement treated at our clinic, can guide dentists in this regard and may be considered as an epidemiological source for the region.